Today's Use of 11th-Century Household Names - Qizi, Uralova Aziza Dilmurod; Kholmirzayevna, Tovasharova Aziza (Research Parks Publishing LLC, 2022)
Even in the eleventh century, people used a variety of household utensils, even though they were far from civilization. In particular, the encyclopedic scholar Mahmud Kashgari in his valuable work gives a large part of these items and tries to explain their core. Devonu lug'atit turk contains the names of many household items, some of which are used in our daily lives under the same name. Another part is the names of obsolete products.